AB0197 Subclinical intersticial lung disease in early rheumatoid arthritis. (15th June 2017) - Fernández-Díaz, C; Calderόn-Goerckel, M; Martin-Varillas, J; Atienza-Mateo, B; Corrales-Martinez, A; Portilla-Gonzalez, V; Calvo-Rio, V; Rueda-Gotor, J; Palmou-Fontana, N; Agudo-Bilbao, M; Vegas-revenga, N; Domingues-Casas, L; et al.
Abstract : Background: Interstitial lung disease (ILD) is a severe extra-articular complication of Rheumatoid Arthritis (RA). The decrease in DLCO diffusion is the most sensitive value for the detection of ILD, DLCO is also a prognostic factor. Objectives: To study the prevalence of subclinical lung involvement in early RA. Methods: Cross-sectional study of lung involvement in early RA. The following criteria were used: A) RA according to the EULAR-2010 criteria. B) Early RA if evolution from the onset of symptoms to the diagnosis of RA was less than one year. C) Lung affectation if DLCO diffusion was lower than 80%. In each patient we evaluate: a) presence of dyspnea according to MMRC (Modified British Medical Research Council) scale; B) Respiratory function tests (FVC, FEV1, FEV1/FVC; C) DLCO; classifying the degree in: i) normal>80% (mild decrease 80–60%); ii) Moderate decrease (60–40%) and iii) Severe reduction (<40%); D) Chest x-ray: assessed by radiologist. E) Joint activity of RA (DAS28), F) CRP and ESR. G) RF, CCPA, H) Presence of atheroma plaque on carotid ultrasound. Quantitative variables were expressed as mean±SD or median [IQR] and were compared with the Student t or Mann Whitney U test, respectively. Dichotomous variables were expressed as percentages and compared using the chi-square test. Statistical analysis was performed with the SPSS 15.0 program. Results: 20 patients (15 women/5 men) with early RA were studied; mean age of 54.1±13.4 years. Some patients were using disease-modifying antirheumatic drugs (DMARDs) prior to performing respiratory function tests (PFR): methotrexate (7) 3 of them with less than 14 days of treatment, hydroxychloroquine (4), sulfasalazine (1). The table shows the main characteristics of patients according to pressence of lung disease. We observed a decrease in DLCO in 15/20 patients (75%) who were mild (DLCO <80%) in 4 (27%); Moderate (DLCO <60%) in 9 (60%) and severe (DLCO <40%) in 2 (13%). Chest x-ray showed these alterations in 3 patients: signs of air trapping, laminar atelectasis and scarring tracts. There were no alterations in FVC in any patient. Conclusions: We find a high frequent of lung involvement in early RA, in most of cases subclinical. Performing Respiratory function tests may help in early detection of lung involvement. These results should be ratified in larger series. Disclosure of Interest: None declared